2017
DOI: 10.1016/j.yexcr.2017.08.016
|View full text |Cite
|
Sign up to set email alerts
|

The functional domains for Bax∆2 aggregate-mediated caspase 8-dependent cell death

Abstract: BaxΔ2 is a functional pro-apoptotic Bax isoform having alterations in its N-terminus, but sharing the rest of its sequence with Baxα. BaxΔ2 is unable to target mitochondria due to the loss of helix α1. Instead, it forms cytosolic aggregates and activates caspase 8. However, the functional domain(s) responsible for BaxΔ2 behavior have remained elusive. Here we show that disruption of helix α1 makes Baxα mimic the behavior of BaxΔ2. However, the other alterations in the BaxΔ2 N-terminus have no significant impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 66 publications
3
32
0
Order By: Relevance
“…Furthermore, bortezomib-induced cell death in BaxΔ2(+) cells is predominantly dependent on the caspase 8/3 pathway ( Fig. 4 ), consistent with our previous findings [ 20 , 23 , 28 ]. BaxΔ2-mediated sensitization of colon cancer cells is not cell line-specific, as a similar behavior was also observed in other colorectal cancer cell lines ( Fig.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Furthermore, bortezomib-induced cell death in BaxΔ2(+) cells is predominantly dependent on the caspase 8/3 pathway ( Fig. 4 ), consistent with our previous findings [ 20 , 23 , 28 ]. BaxΔ2-mediated sensitization of colon cancer cells is not cell line-specific, as a similar behavior was also observed in other colorectal cancer cell lines ( Fig.…”
Section: Discussionsupporting
confidence: 92%
“…We have previously shown that BaxΔ2 induces cell death through activation of caspase 8 [ 23 , 28 ]. To determine whether the proteasome inhibitor-induced cell death could also be through BaxΔ2-meditated activation of caspase 8, BaxΔ2(+) cells were treated with proteasome inhibitors for 24 h, and analyzed for BaxΔ2 expression and caspase 8 activation by immunoblotting.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is generally believed that generation of Bax∆2 requires a microsatellite frameshift mutation in combination with an alternative splicing event that restores the reading frame. Like Baxα, Bax∆2 is pro-apoptotic and has similar characteristics, such as binding with Bcl-2; however, Bax∆2 does not target mitochondria, and instead activates a caspase 8-dependent death pathway (Haferkamp et al 2012;Zhang et al 2014;Mañas et al 2017). In the process of analyzing the expression and distribution of Bax∆2 throughout the human body, we examined several tissue sections of human brain.…”
Section: Introductionmentioning
confidence: 99%